Interactions between Classroom Discourse and Cultural Identities - Kettani, Moulay Tahar; Ouahidi, Lalla Meriem (International Journal of Language and Literary Studies, 2025)
This article investigates the relationship between classroom discourse, student identities, and teacher ones, and how a reciprocal influence takes place, affecting the three constructs. Throughout the literature, many studies confirmed the fact that classroom discourse is heavily impacted by social norms and professional constraints, as well as the identities that manifest through continuous interactions. Teacher identity is also found to be influenced by professional dictations like work ethics, personal beliefs, and values, as well as interactions with their own students. Along with that, many studies asserted that student identity is a flexible and sensitive construct easily influenced by school and teachers’ expectations, the interactions that take place between peers, and the diverse cultural backgrounds that thrive at school. This review also highlights the reciprocal influence between some teachers’ identities, that manifest in certain discursive practices, and student identities that either validate teachers’ input or resist it. Some case studies were reviewed offering more confirmation of the imperative of adopting more considerate and inclusive approaches while scaffolding the process of discursive identity construction; eventually optimizing relatedness, well-being, and academic performance.